Counting missing women: a reconciliation of flow and stock measures - Cara Ebert; Stephan Klasen; Sebastian Vollmer (Journal of Population Economics, 2025)
Abstract Stock estimates of missing women suggest that excess female deaths are concentrated in South and East Asia and among young children. In contrast, flow estimates suggest that gender bias in mortality is much larger than previously estimated using stock measures, is as severe among adults as it is among children in India and China, and is larger in Sub-Saharan Africa than in India and China. We show that the different stock and flow measure results rely on the choice of the reference standard for mortality and an incomplete correction for different disease environments in the flow measure. Alternative reference standards reconcile the results of the two measures.
Additional information: J16;D63;I14;I15;O15
Keywords: 330; Missing women; Gender bias; Mortality; Disease; Age; Sub-Saharan Africa; China; India